2021
DOI: 10.1002/ps.6369
|View full text |Cite
|
Sign up to set email alerts
|

The potential of pro‐insecticides for resistance management

Abstract: Pro‐insecticides have been a significant part of the insecticide market for decades. Bioactivation of such compounds is generally an enzyme‐controlled process, in which the target insect metabolizes the pro‐form into an active compound. This approach has several potential advantages, including improved bio‐kinetic properties and safety profiles of the pro‐insecticide relative to the active form. A less common advantage of pro‐insecticides is increased activity on metabolically resistant strains. Specific cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 54 publications
0
25
0
4
Order By: Relevance
“…Some studies have demonstrated that detoxifying enzymes (P450s) in mosquitoes that are responsible for converting parent chlorfenapyr (CL303630) to its pro-insecticide metabolite (CL303268) can be inhibited with known inhibitors like PBO in measurable ways both in vivo and in vitro [ 29 , 43 , 44 ]. To less experienced researchers with this mode of action, the tendency to assume resistance rather than poor conversion (from parent to pro-insecticidal metabolite) requires consideration of laboratory or field-testing conditions which might interfere with chlorfenapyr’s mode of action [ 29 , 38 ] as influenced by numerous endogenous and exogenous elements [ 21 ]. Other studies point to induction routes which favor pre-exposures to neurotoxic chemistries (e.g., alpha-cypermethrin or others) which may actually enhance the conversion rates of the more toxic form of chlorfenapyr to mosquitoes as do more metabolically resistant mosquito strains (68,74).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated that detoxifying enzymes (P450s) in mosquitoes that are responsible for converting parent chlorfenapyr (CL303630) to its pro-insecticide metabolite (CL303268) can be inhibited with known inhibitors like PBO in measurable ways both in vivo and in vitro [ 29 , 43 , 44 ]. To less experienced researchers with this mode of action, the tendency to assume resistance rather than poor conversion (from parent to pro-insecticidal metabolite) requires consideration of laboratory or field-testing conditions which might interfere with chlorfenapyr’s mode of action [ 29 , 38 ] as influenced by numerous endogenous and exogenous elements [ 21 ]. Other studies point to induction routes which favor pre-exposures to neurotoxic chemistries (e.g., alpha-cypermethrin or others) which may actually enhance the conversion rates of the more toxic form of chlorfenapyr to mosquitoes as do more metabolically resistant mosquito strains (68,74).…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic transformation of parent chlorfenapyr (CL303630) to its pro-insecticidal metabolite (CL303268) can be slow and quite variable, but generally unidirectional once conversion has started [29]. The uncoupling of oxidative phosphorylation can be influenced by many exogenous and endogenous factors: temperature, cuticular penetrations, physical movement of challenged insects, host-seeking behaviors, PLOS NEGLECTED TROPICAL DISEASES blood-feeding status of mosquitoes, concentrations of chlorfenapyr challenged to insects from different substrates, degree of metabolic activity already within target pests and antagonisms by known metabolic inhibitors or competing resistant mechanisms (e.g., Glutathione S-Transferases or GSTs are not known to favor similar intoxication routes as cytochrome P450s) [21,29,37,38]. Ultimately, as chlorfenapyr is a physiological toxin, normal mosquito behaviors during their circadian rhythms will favor intoxication [19,20] and its evaluation in small cages may yield different (poorer) results compared to experimental houses.…”
Section: Discussionmentioning
confidence: 99%
“…In his mini‐review, David asks the question of whether pro‐insecticides could have a natural advantage in the control of metabolically resistant insects due to their need for bioactivation 6 . Can pro‐insecticides use the increased metabolism of such insect strains against them by increasing the rate or extent of their metabolic bio‐activation?…”
Section: Reviews Mini‐reviews and Perspectivesmentioning
confidence: 99%
“…Менее распространенное преимущество проинсектицидов -повышенная активность в отношении метаболически устойчивых популяций насекомых. Конкретные случаи, когда проинсектицид демонстрирует отрицательную перекрестную резистентность к метаболически устойчивой популяции из-за повышенной биоактивации проинсектицида, неоднократно отмечались за последние 50 лет (Salgado, David, 2017, Das, Mukherjee, 2018, David, 2021. Так, например, показана большая инсектицидность проинсектицида хлорфенапира (группа пирролов) для резистентных к пиретроидам комаров рода Culex (Yuan et al, 2015, Raghavendra et al, 2011 и мух-жигалок Haematobia irritans (Sheppard, Joyce 1998).…”
Section: заключениеunclassified